2015
DOI: 10.1055/s-0035-1545845
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Natural Products against Prostate Cancer: Mechanism of Action and Autophagic/Apoptotic Molecular Pathways

Abstract: Introduction !Prostate cancer (PCa) is one of the most common malignancies in men and a leading cause of death worldwide for men. Taking into consideration that chemotherapy has severe side effects and usually a poor outcome, there is an intensive need for the development of safer and more effective agents. Since plants have been used by traditional medicine for the treatment of various diseases, in the last decades, many natural products have been isolated from plants and tested for their tumor selectivity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 192 publications
1
11
0
Order By: Relevance
“…Nevertheless, Davis-Searles et al showed that several compounds of the extract such as silybin B, isosilybin B, and taxifolin are effective in PC-3 cells [4]. Our findings coincide overall with previous studies that depict silymarinʼs and silibininʼs antiproliferative properties in a variety of cancer types in preclinical models [3]. Furthermore, the co-treatment with DXR-SEE and DXR-silibinin resulted in a substantial inhibition of cell proliferation even at very low doses of DXR (< 3 nM), suggesting a significant additive effect, as SEE and silibinin are able to lower the cytotoxic dose of DXR.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Nevertheless, Davis-Searles et al showed that several compounds of the extract such as silybin B, isosilybin B, and taxifolin are effective in PC-3 cells [4]. Our findings coincide overall with previous studies that depict silymarinʼs and silibininʼs antiproliferative properties in a variety of cancer types in preclinical models [3]. Furthermore, the co-treatment with DXR-SEE and DXR-silibinin resulted in a substantial inhibition of cell proliferation even at very low doses of DXR (< 3 nM), suggesting a significant additive effect, as SEE and silibinin are able to lower the cytotoxic dose of DXR.…”
Section: Discussionsupporting
confidence: 91%
“…Hence, there is an urgent need to discover new supplementary treatments in order to reduce DXR cytotoxicity in normal cells without affecting and even enhancing its antitumor potential [2]. Over the last years, several natural dietary compounds have been tested for their cytotoxic or antitumor activity, showing promising results as they prevent the occurrence and/or spread of cancer either alone or in combination with chemotherapeutical agents [3]. SEE is a natural preparation obtained from the seeds of milk thistle (Silybum marianum [L.] Gaertn., Asteraceae), comprising of a number of flavonolignans and flavonoids, with silibinin (silybin A and silybin B) being the major bioactive component [4].…”
Section: Introductionmentioning
confidence: 99%
“…Natural compounds can induce the apoptosis of cancer cells by triggering caspase and mitochondria-dependent cascades, by inhibiting oncogenes, or by suppressing NFκB signaling ( Gioti and Tenta, 2015 ; Zhou et al, 2015 ). We herein demonstrated that OPD′ could induce apoptosis in PC3 cells via a caspase-independent pathway.…”
Section: Discussionmentioning
confidence: 99%
“… 16 - 26 Phytochemical studies of the genus Bursera have reported the presence of lignans, bilignans, flavonoids, flavonoid glycosides, steroids, short-chain aliphatic alkanes, acetates, alcohols, ketones, and terpenoids, the latter mostly monoterpenes while diterpenes and triterpenes occur at lesser extent. 5 , 6 , 18 , 27 - 33 Secondary metabolites belonging to these groups of compounds have been reported to have cytotoxic properties, 34 - 36 further suggesting a potential use of Bursera extracts in the treatment of cancer. Accordingly, extracts of B. ariensi, B. bicolor, B. linanoe, B. galeottiana, B. fagaroides, B. graveolens, B. microphylla , and B. schlechtendalli have been found to induce growth inhibitory effects in different cancer cell lines, and extracts from B. fagaroides, B. permollis, B. morelensis, B. microphylla, B. klugii , and B. schlechtendalii have also been shown to exert antitumor activity in mice.…”
Section: Introductionmentioning
confidence: 99%